Association of Mesocotyl and Coleoptile Elongation with Seedling Vigor and Yield and its Components in Rice - T. Metwally; M. M. A. Osman; R. El-Namaky; Haytham M. El Sharkawi (Global Journal of Agricultural Innovation, Research & Development, 2016)
The present study was carried out at laboratory, greenhouse and experimental farm of Rice Research and Training Center (RRTC), Sakha, Kafr El-Sheikh, Egypt during 2014 and 2015 season to investigate the differences in some seedling vigor, yield and its attributes and Nitrogen (N) status in milled grain which measured on eight rice varieties i.e. Giza 171, Giza 177, Giza 178, Sakha 101, Sakha 102, Sakha 103, Sakha 104 and Gaori. The results revealed that the short stature genotypes Sakha101 and Gaori (91.0 and 77.95cm) gave shortest Mesocotyl length and plant height. Where as, the tall plants of Giza171, Sakha 102 (126 and 106cm) had comparatively long mesocotyl. Also, the data indicated that tall plants tend to produce long coleoptile while semi-dwarf or short genotypes produced short ones. Sakha 101 and Giza 178 rice cultivars recorded the highest values of panicles m-2, grains panicle-1, grain yield t ha-1, biomass production t ha-1 and harvest index. Nitrogen and protein content in milled grain was statistically higher in the genotype Gaori than other entries while the genotypes Sakha 101 and Sakha 103 uptake more nitrogen than the others. The results suggested that varieties of Giza177, Sakha102 and 104 are more tolerant to adverse conditions during seeding stage.